THE APPEARANCE OF FALSE SIGN IN ADS AT SOCIAL MEDIA - Ilhamsyah, Ilhamsyah; Herlina, Herlina (ELT Perspective Jurnal Pendidikan Bahasa Inggris, 2016)
Abstract The aim of this study is to determine the presence of signs and combinations of signs (codes) that are present on the fictitious figure of Sarah Aprilia in Cologne Bask advertising on the internet. The sign and the code in general should have a common understanding by prospective readers (target audience). This research used qualitative approach with interpretative descriptive method because semiotic science is digging and discovery the meaning. In analyzing the fictitious figure of Sarah Aprilia, the sign that appearance is false sign. Deceptive mark is a sign that unknown origin , but the engineering rests on a natural object (hybrid), but viewers assume it was real presence. This is due to the many cross signs presented visual codes that make the figure of Sarah Aprilia as a real figure. Keywords : Advertising , Semiotics, Signs, Digital Media